Antibacterial activity of purified papaya leaf (Carica papaya L.) fraction emulgel as anti-acne against Staphylococcus aureus - Dewi Putri Husain; Arif Budi Setianto; Kintoko (Universitas Ahmad Dahlan, 2026)
Acne (acne vulgaris) is a skin disorder caused by Staphylococcus aureus. Continuous antibiotic use for acne management was reported to cause resistance, so alternative treatments using natural ingredients were needed. Papaya leaves can be formulated into dosage forms to facilitate their use. This study aims to investigate the antibacterial activity of the purified papaya (Carica papaya L.) leaf emulgel fraction against Staphylococcus aureus. The research was carried out by extracting simplicia powder by maceration with 70% ethanol, and the crude extract was purified using distilled water: n-hexane (1:1) mixture. The crude extract and purified fraction of papaya (Carica papaya L.) leaves were tested for their compound content using phytochemical screening. The purified fraction was formulated into an emulgel dosage form and tested for anti-acne activity using the well method. Data were analyzed using SPSS with a one-way ANOVA. The results of phytochemical screening tests showed that crude extracts and purified fractions contained alkaloids, flavonoids, tannins, saponins, and terpenoids. Physicochemical tests of the 2% purified fraction emulgel show a pH of 5.23, viscosity of 10.74 Pa·s, dispersion of 6.08 cm, and adhesion of 10.07 seconds. The 3% purified fraction emulgel has a pH of 5.56, viscosity of 7.34 Pa·s, dispersion of 7.1 cm, and adhesion of 2.92 seconds. The 5% purified fraction emulgel has a pH of 5.56, viscosity of 0.49 Pa·s, dispersion of 7.1 cm, and adhesion of 2.92 seconds. The inhibition zones of the purified fraction, crude extract, and purified fraction emulgel of 2%, 3%, and 5% concentrations were 7.9 mm ± 0.44, 5.7 mm ± 0.3, 8.3 mm ± 0.21, 9.04 mm ± 0.28, and 9.56 mm ± 0.25, respectively. The conclusion, two of the three preparations met the physicochemical standard, namely, the 2% and 3% purified fraction emulgels. The purified fraction emulgel was more effective against bacteria than the crude or pure extracts (p < 0.05).